THE APPLICATION OF PROBLEM POSING LEARNING THEME INTEGRATED BOTANY IN STATE SENIOR-HIGH-SCHOOL GRADE XI - KINANTI AYU PUJI LESTARI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Problem posing learning model was a learning model that assign students to made questions about the material being taught which must then be solved by students either individually or in groups. Reformulate the problem or application problem is one way to make progress in solving the problem. Learn to ask very important in the educational process. Students can not have learned before asked himself, and then answer the question. It is a reflection of the problem posing learning model. Students will got direct experience by doing activities related to the integrated botanical material. This learning model aims to achieve competency in accordance with theme integrated botany in the structure and function of plant tissue is taught. This type of research was a pre-experimental research The method used was the “One Group Pre-test – Post-test” with subjects 26 students class XI Science 1 SMAN 1 Gresik Manyar. The analysis was conducted in descriptive quantitative. Cognitive learning outcomes students, 88.47% of students have completed the classical. Based on the obtained results it can be concluded that the problem posing effective learning model applied to an integrated botanical material. Keywords: Problem Posing Learning, Students Learning Achievement, Integrated botany.